Prevalence of a characteristic gene profile in high-level rhythmic gymnasts - Tringali, C.; Brivio, I.; Stucchi, B.; Silvestri, I.; Scurati, R.; Michielon, G.; Alberti, G.; Venerando, B. (Journal of Sports Sciences, 2014)
High-level physical performance in rhythmic gymnastics is influenced by numerous skills and anthropometric factors. In order to understand if genetic predisposition could play a role to define the elite rhythmic gymnast phenotype, we analysed the frequency of common polymorphisms linked to genes correlated with body mass (ADRB2 and FTO), explosive strength (ACTN3 and ACE), and joint mobility (COL5A1), in 42 gymnasts involved in National and International events, and in 42 control girls. Our results demonstrated that high-level rhythmic gymnasts constituted a genetically selected population showing higher frequency of: (a) ADRB2 and FTO alleles linked to low body mass index and low fat mass; (b) COL5A1 CT genotype linked to high joint mobility and to the occurrence of genu recurvatum, but also to a higher incidence of injuries. ACTN3 and ACE polymorphisms did not appear to be connected with the phenotype of high-level rhythmic gymnast. Based on these data, it can be assumed that these polymorphisms could positively affect the phenotype and performance of gymnasts.